Comparison of Semiconductor Optical Amplifier and Discrete Raman Amplifier Performance in DWDM Systems - Olonkins, S.; Bobrovs, V.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2012)
In the last decade due to the growing demand on high capacity transmission, DWDM transmission systems have evolved rapidly. The growth of transmission speed and the decrease in channel spacing has resulted in stricter requirements to the elements used in optical signal transmission process, including optical amplifiers. In this article we take one of the most popular DWDM solutions – a 10 Gbit/s 16 channel NRZ-OOK 50 GHz DWDM transmission system, and implement a SOA and a RA as a single in-line amplifier, in order to estimate and compare their performance, and to identify and estimate the main factors that limit the total transmission quality in both cases. Ill. 6, bibl. 6, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2392